Effect of resistance training on strength and endurance of muscle in chronic heart failure - Wungouw, Herlina (Lembaga Penelitian Universitas YARSI, 2009)
Resistance training (RT) has been used to increase muscle strength and endurance. In CHF patients, the effect of RT has not been thoroughly investigated. This study was conducted to explore the effect of RT to reverse muscular weaknesses and decreased muscular endurance that have been found in many CHF patients.A prospective-randomized controlled study was used as the research design. The effect of RT on muscular strength and endurance was evaluated in 39 CHF patients with II-III New York Heart Association (NYHA) functional class and left ventricle ejection fraction (LVEF), 27+7 (mean + standard deviation) in the exercise group and 28+6 in the control group. Initial two tests, knee extensor/flexor and elbow extensor/flexor for measuring strength and endurance were performed one week apart using isokinetic machine. After randomization (exercise group=EG and control group=CG), EG performed 3 months supervised RT in hydraulic machine using incremental approach based on individual response. All patientsfollowed the end-point test.The result showed that muscular strength and endurance in EG increased by 20+19% (p <.000) and 25+26% (p < .001), respectively while in the CG, strength and endurance nearly unchanged. The difference between groups was significant (p< .006 for strength and p < .003 for endurance). There was no adverse cardiac event occurred during the test and training sessions.In conclusion, resistance training was safe for stable CHF patients and was able to increase muscular strength and endurance.